Speed boost from the core: a pilot study on core strength training in young male Chinese hockey athletes - Soh, Kim Geok; Samsudin, Shamsulariffin; Ma, Hucheng (Universiti Putra Malaysia, 2024)
Speed is a critical component of athletic performance, particularly in sports like field hockey, where quick movements and agility are essential. However, limited research has examined the effects of core strength training on speed performance in youth athletes. This study aimed to investigate the impact of core strength training on the speed performance of young male field hockey players in China. A cluster randomised controlled trial (C-RCT) was conducted with participants aged 15 to 17, who were assigned to either a core strength training group (CSTG) or a control group (CTG). The intervention lasted two weeks, with assessments of speed performance conducted at baseline and post-intervention. Although no significant differences were observed in overall speed levels between the groups, the CSTG showed a notable improvement in speed performance compared to the CTG, achieving statistical significance. These findings suggest that core strength training can positively influence speed performance in young male field hockey players and underscore the importance of incorporating such training into athletic programs to optimize speed outcomes in this population.